Assessment of Daytime and Nighttime Ground Level Ozone Pollution in Malaysian Urban Areas - Ahmad A.N.; Abdullah S.; Mansor A.A.; Dom N.C.; Ahmed A.N.; Ismail N.A.; Ismail M. (Universiti Putra Malaysia Press, 2024)
Introduction: Ozone (O3) is a significant component of photochemical smog as a typical secondary which is formed via nitrogen oxide photochemical interactions with volatile organic compounds (VOCs). This research discerns the complex influence of meteorological parameters and air pollutants influencing O3 concentrations. Methods: Data were acquired from 1 January 2018 until 31 December 2020 that including ozone (O3), nitrogen oxide (NOx), nitric oxide (NO), sulphur dioxide (SO2), nitrogen dioxide (NO2), carbon monoxide (CO), particulate matter (PM10, PM2.5), wind speed, solar radiation, temperature, and relative humidity (RH). Data were analysed using descriptive statistics in terms of line graphs. Results: The results demonstrate that the O3 concentration peaked around 14:00 hours and dropped at night (20:00 hours) owing to the lack of sunshine and redox processes. Conclusion: In conclusion, ozone precursors played an important role in ozone formation and the findings of this research are valuable for policymakers and other interested parties. 2023 UPM Press. All rights reserved.